Molecular analysis of host cells response against infection of virulent strains Listeria monocytogenes / Maimunah Mustakim , Zuraini Mat Issa and Prof Dr Son Radu - Mustakim, Maimunah; Mat Issa, Zuraini; Prof Dr Son Radu (Research Management Institute (RMI), 2014)
Listeria monocytogenes is a foodborne pathogenic bacteria causing severe systemic infection in susceptible individuals. This facultative intracellular pathogen infects host tissues using their flagella actin. Listeria monocytogenes propelled from one cell to another through the assembly of the flagella actin with the host cells.The present study aims to examine the rearrangement of host cells cytoskeleton actin upon infection of Listeria monocytogenes. Human colon carcinoma (HCT 116) cell lines were infected with Listeria monocytogenes strains. Cells were stained withalexa fluor 635 phalloidin prior to observation by confocal laser scanning microscopy (CLSM) to examine cellular changes of the host cells upon infection with the bacteria. The infected cells showed actin rearrangement from filamentous network to aggregation features. The infected cells also showed reduced membrane ruffling. The present study demonstrated interaction of host cells actin with Listeria monocytogenes. Confocal laser scanning microscope (CLSM) examination revealed the cytoskeleton actin rearrangement in the infected host cells.